Technology to support mental health adolescents: a literature review - Lina Handayani; Heni Trisnowati; Isah Fitriani; Beddu Hafidz; Asa Ismia Bunga Aisyahrani (International Journal of Public Health Science (IJPHS), 2026)
The increasing prevalence of mental health issues among adolescents highlights a critical public health concern. Adolescents face unique challenges during this developmental phase, including academic pressure, social media influence, and the stigma surrounding mental health, which may hinder their willingness to seek help. This paper aims to explore the role of technology in preventing and addressing mental health challenges among adolescents, focusing on the potential of digital tools to provide accessible and effective support. This study is a literature review using the PRISMA method, covering articles published between 2001 and 2024. A total of 56 relevant articles were retrieved from the Science Direct, Scopus, and Google Scholar databases. This study seeks to analyze technological interventions in mental health care. The primary strategies include examining mobile applications, telehealth services, and other digital platforms that facilitate early detection and the sustainable management of mental health conditions. The review also considers the implications of privacy, data security, and digital literacy in implementing technology. Findings indicate that digital tools can significantly enhance access to mental health resources, enable timely interventions, and reduce the stigma associated with seeking help.A comprehensive approach that combines technological innovation with robust data protection is crucial to improving adolescent mental well-being. By leveraging the power of technology while ensuring personal information security, stakeholders in mental health, technology, and policy can collaborate to create effective, accessible, and safe mental health interventions for young people.